(untitled) (Journal of Laboratory Animal Science, 2018)
Cyclophosphamide is a DNA non-intercalating agent with wide application against several human neoplasms. It is found that caffeine alters protection against cytogenotoxicity of different chemicals and physical mutagens including cyclophosphamide. Modulation of the clastogenic induced effect of cyclophosphamide by three different doses of caffeine (25, 50 and 100 mg/kg) was assessed through the chromosomal aberration and mitotic index studies in bone marrow cells. Micronucleus level were decreased significantly (28.8%) in 100 mg caffeine treated group at 30 h post treatment. Results revealed that caffeine decreased the cyclophosphamide induced chromosomal aberration and mitotic index in bone marrow cells. In the present study, the percentage of dividing cells were reduced more in the mice pre-treated with CAF at the dose rate of 100 mg/kg than with lower doses of CAF in all the three anticancer drugs tested. Thus, CAF modulation is expected to play an important role in the development of cancer chemotherapy. The protective effect of caffeine was found to be dose dependent. However, further study on the mechanism of quenching of free radicals and induction of apoptosis by caffeine are required to substantiate the results.